The Impact of group guidance in alleviating parental anxiety amidst the Menace of child abduction - Putra, Ahmad; Deliani, Nurfarida; Fitria, Anggi; Halim, Candra; Dzunuren, Arifal; Mulya, Sri (Journal of Advanced Guidance and Counseling, 2023)
Purpose - This research was conducted to see how the effectiveness of group guidance services in helping reduce the anxiety experienced by parents of SDN 41 Karang Tangah students regarding the issue of child kidnapping that is spread in the midst of society.Method - The type of research used is descriptive qualitative, the researchers involved 5 mothers of SDN 41 Karang Tangah students as group guidance participants with the aim of alleviating the anxiety experienced with the current issue of child abduction.Result  -  This topic at least generates several important points for parents, including: first, parents realize that advances in technology and social media make it easy for various issues to develop in the midst of society, second, parents find new knowledge and wise ways to deal with developing issues, third, parents understand that excessive anxiety will only lead to various forms of illness and weaken health conditions, fourth, parents understand how to properly supervise children, fifth, parents feel relieved and happy to be able to convey all aspirations and anxiety related to the growing issue of child abduction.Implication – Parents of students at SDN 41 Karang Tangah West Sumatra who were involved in group guidance activities discussed the topic of the task which was directly determined by the group leader with the topic "the issue of child abduction and the role of parents in dealing with it".Originality - Amidst the tension and concern over the threat of child abduction, an interesting thematic novelty is the emergence of new approaches to address parental anxiety. Group guidance emerged as a promising solution, providing a platform for sharing experiences and strategies, which in turn can reduce anxiety levels.***Tujuan - Penelitian ini dilakukan untuk melihat bagaimana efektivitas layanan bimbingan kelompok dalam membantu mengurangi kecemasan yang dialami oleh orang tua siswa SDN 41 Karang Tangah terhadap isu penculikan anak yang tersebar di tengah-tengah masyarakat.Metode - Jenis penelitian yang digunakan adalah deskriptif kualitatif, peneliti melibatkan 5 orang ibu dari siswa SDN 41 Karang Tangah sebagai peserta bimbingan kelompok dengan tujuan untuk mengurangi kecemasan yang dialami dengan adanya isu penculikan anak yang sedang marak saat ini.Hasil - Topik ini setidaknya menghasilkan beberapa poin penting bagi orang tua, antara lain: pertama, orang tua menyadari bahwa kemajuan teknologi dan media sosial memudahkan berbagai isu berkembang di tengah-tengah masyarakat, kedua, orang tua menemukan pengetahuan baru dan cara-cara yang bijak dalam menyikapi isu-isu yang berkembang, ketiga, orang tua memahami bahwa rasa cemas yang berlebihan hanya akan menimbulkan berbagai macam penyakit dan melemahkan kondisi kesehatan, keempat, orang tua memahami bagaimana cara pengawasan yang tepat terhadap anak, kelima, orang tua merasa lega dan senang dapat menyampaikan semua aspirasi dan kegelisahannya terkait isu penculikan anak yang berkembang.Implikasi - Orang tua siswa SDN 41 Karang Tangah Sumatera Barat yang terlibat dalam kegiatan bimbingan kelompok membahas topik tugas yang langsung ditentukan oleh pemimpin kelompok dengan topik "isu penculikan anak dan peran orang tua dalam menghadapinya".Orisinalitas - Di tengah ketegangan dan kekhawatiran akan ancaman penculikan anak, kebaruan tematik yang menarik adalah munculnya pendekatan baru untuk mengatasi kecemasan orang tua. Bimbingan kelompok muncul sebagai solusi yang menjanjikan, menyediakan platform untuk berbagi pengalaman dan strategi, yang pada akhirnya dapat mengurangi tingkat kecemasan.